The CRY1-HsF predicted interaction interface serves as a molecular platform for bioengineering or selecting modulating mutants - Jmii, Souleïmen; Bouard, William; Marcotte, Gabriel; Plamondon, Julien; Cappadocia, Laurent (Frontiers in Plant Science, 2025)
IntroductionHigh-temperature stress imposes an energetic cost on plant growth and negatively impacts agricultural productivity. This stress rapidly triggers the activation of Heat shock Factor (HsF) proteins, a family of transcription factors that maintain proteostasis. The cryptochrome CRY1 can physically interact with HsFA1d proteins to facilitate nucleus translocation and the regulation of genes that contributes to stress tolerance.MethodsWe combined structural predictions with experimental testing using yeast-two-hybrid and bimolecular fluorescence complementation assays.ResultsWe confirm that CRY1 PHR domain interacts extensively with multiple HsF proteins through their HR-A region of the conserved oligomerization HR-A/B domain interface. This interaction partially relies on salt bridges provided by the N- and C-terminus of HR-A region and a conserved interface centered around W352 of CRY1. HsFA3 shows the strongest affinity to CRY1 in yeast-two-hybrid assays notably thanks to a glutamate residue that interacts with R211 and R435 of CRY1. Mutating equivalent residue positions within HsFA1e or HsFC1 to a glutamate increased their interaction to CRY1.DiscussionOverall, our analysis allowed the identification of mutant candidate that could be used in selection or bioengineering endeavors to improve thermal stress tolerance.